Draft Annual Plan 2010-2011 Volume-II B (Statistical Tables) - Planning Commission (Planning Commission, 2010)
Proposed Physical Targets For Annual Plan 2010-11 Physical Targets & Anticipated Achievements 2009-10 Physical Targets & Actual Achievements 2008-09 Statement Regarding Externally Aided Projects Bharat Nirman Programmes Centrally Sponsored Schemes A Tribal Sub Plan (TSP): Financial Outlays Special Component Plan For Scheduled Castes (SCSP -1) Financial Outlays Financial Outlays / Expenditure For Voluntary Sector 298-305 A Women Component In the State Plan Programme Financial Outlays.
(Statistical Tables)